2021
DOI: 10.1128/mbio.02600-21
|View full text |Cite
|
Sign up to set email alerts
|

A Histone Deacetylase, Magnaporthe oryzae RPD3, Regulates Reproduction and Pathogenic Development in the Rice Blast Fungus

Abstract: RPD3 is an evolutionarily conserved class I histone deacetylase (HDAC) that plays a pivotal role in diverse cellular processes. In filamentous fungal pathogens, abrogation of the gene encoding RPD3 results in either lethality or severe growth impairment, making subsequent genetic analyses challenging. Magnaporthe oryzae is a causal agent of rice blast disease, which is responsible for significant annual yield losses in rice production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Dep1, a component of Rpd3L complex, controls vegetative development, ROS accumulation, and pathogenesis in F. pseudograminearum [ 117 ]. However, Rpd3 disruption in several filamentous fungi, such as A. nidulans , A. fumigatus , B. cinerea and M. oryzae , is lethal [ 110 , 118 , 119 ]. Overexpression of Rpd3 in B. cinerea and M. oryzae results in dramatically impaired infection structure formation, oxidative stress response, and virulence [ 118 , 120 ].…”
Section: Histone Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dep1, a component of Rpd3L complex, controls vegetative development, ROS accumulation, and pathogenesis in F. pseudograminearum [ 117 ]. However, Rpd3 disruption in several filamentous fungi, such as A. nidulans , A. fumigatus , B. cinerea and M. oryzae , is lethal [ 110 , 118 , 119 ]. Overexpression of Rpd3 in B. cinerea and M. oryzae results in dramatically impaired infection structure formation, oxidative stress response, and virulence [ 118 , 120 ].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Transcription of enzymatic genes are negatively controlled by Rpd3-mediated H3 deacetylation in B. cinerea [ 118 ]. Moreover, Rpd3 is implicated to be potentially involved in the TOR (target of rapamycin)-mediated signaling pathway to regulate fungal reproduction and pathogenic development in M. oryzae [ 119 ]. The line of evidence shows that Rpd3 is essential for the survival of plant pathogenic fungi, suggesting that RPD3 could be a promising target for identification and development of new agrochemicals that can effectively control fungal diseases in crop plants [ 121 ].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…The NuA3 complex may recruit more Fng3 to enhance the FgSas3 HAT activity when the interaction between Fng3 and FgRpd3 was disrupted, suggests an equilibrium between NuA3 HAT and Rpd3 HDAC activities. In comparison with yeast Rpd3, FgRpd3 and its orthologs from N. crassa (Smith et al ., 2010) and M. oryzae (Lee et al ., 2021) have an extra C‐terminal tail region that is unique to filamentous ascomycetes. Further characterization showed that the C‐terminal region of FgRpd3 was responsible for its interaction with Fng3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MoRpd3 was able to complement yeast deletion mutant of Rpd3. Whereas MoRpd3 without C‐terminal tail could only partially do (Lee et al ., 2021), suggests the C‐terminal tail of MoRpd3 is not limited to provide platform for interaction with other proteins such as Fng3. Indeed, multiple frame‐shift mutation in the C‐terminal region of FgRpd3 was suppressive to the fng1 mutant in F. graminearum , indicated that the C‐terminal region of FgRpd3 also was functionally related to Fng1 (H. Jiang et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ahc1p (Ada Histone acetyltransferase complex Component) is a unique subunit of the ADA complex that is essential for its structure and function ( Culbertson and Shogren-Knaak, 2021 ). In addition, nucleosome acetyltransferase of H4 (NuA4) is also a critical acetyltransferase complex in eukaryotes ( Sathianathan et al, 2016 ), and its subunit Eaf3p (Esa1p-Associated Factor) is also a subunit of the deacetylase complex Rpd3S ( Biswas et al, 2008 ; Okuda and Nishimura, 2020 ; Lee et al, 2021 ). Eaf3p identifies the corresponding histone methylation sites through the N-terminal chromodomain of the nucleosome in the gene-coding region to locate NuA4 and Rpd3S ( Ruan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%